The Record Keeper - Book 3 - Martin, Charles, 1969- (Thorndike, Maine : Center Point Large Print, 2022)
"Murphy Shepherds last rescue mission very nearly cost him his life. Hed like nothing more than to stay close to his wife and daughters for a while. But Boness brother must be stopped, and there are so many who need to know that they are worth rescuing. As the cat-and-mouse game moves into the open, Murphy is tested at every turn--both physically and mentally. And then the unthinkable happens: his beloved mentor and friend is taken. Without a trace. Murphy lives by the mantra that love shows up. But how can he do that when he has no leads? With heart-stopping clarity, The Record Keeper explores the true cost of leaving the ninety-nine to find the one."--
Keywords: Human trafficking -- Fiction; Search and rescue operations -- Fiction; Missing persons -- Investigation; Fiction; Thrillers (Fiction); Christian fiction